Risk factors for thromboembolic and bleeding events in anticoagulated patients with atrial fibrillation: the prospective, multicentre observational PREvention oF thromboembolic events - European Registry in Atrial Fibrillation (PREFER in AF). Issue 3 (30th March 2019) - Rohla, Miklos; Weiss, Thomas W; Pecen, Ladislav; Patti, Giuseppe; Siller-Matula, Jolanta M; Schnabel, Renate B; Schilling, Richard; Kotecha, Dipak; Lucerna, Markus; Huber, Kurt; De Caterina, Raffaele; Kirchhof, Paulus
Abstract : Objectives: We identified factors associated with thromboembolic and bleeding events in two contemporary cohorts of anticoagulated patients with atrial fibrillation (AF), treated with either vitamin K antagonists (VKA) or non-VKA oral anticoagulants (NOACs). Design: Prospective, multicentre observational study. Setting: 461 centres in seven European countries. Participants: 5310 patients receiving a VKA (PREvention oF thromboembolic events - European Registry in Atrial Fibrillation (PREFER in AF), derivation cohort) and 3156 patients receiving a NOAC (PREFER in AF Prolongation, validation cohort) for stroke prevention in AF. Outcome measures: Risk factors for thromboembolic events (ischaemic stroke, systemic embolism) and major bleeding (gastrointestinal bleeding, intracerebral haemorrhage and other life-threatening bleeding). Results: The mean age of patients enrolled in the PREFER in AF registry was 72±10 years, 40% were female and the mean CHA2 DS2 -VASc Score was 3.5±1.7. The incidence of thromboembolic and major bleeding events was 2.34% (95% CI 1.93% to 2.74%) and 2.84% (95% CI 2.41% to 3.33%) after 1-year of follow-up, respectively. Abnormal liver function, prior stroke or transient ischaemic attack, labile international normalised ratio (INR), concomitant therapy with antiplatelet or non-steroidal anti-inflammatory drugs, heart failure and older age (≥75 years) were independently associated with both thromboembolic and major bleeding events. With the exception of unstable INR values, these risk factors were validated in patients treated with NOACs (PREFER in AF Prolongation Study, 72±9 years, 40% female, CHA2 DS2 -VASc 3.3±1.6). For each single point decrease on a modifiable bleeding risk scale we observed a 30% lower risk for major bleeding events (OR 0.70, 95% CI 0.64 to 0.76, p<0.01) and a 28% lower rate of thromboembolic events (OR 0.72, 95% CI 0.66 to 0.82, p<0.01). Conclusion: Attending to modifiable risk factors is an important treatment target in anticoagulated AF patients to reduce thromboembolic and bleeding events. Initiation of anticoagulation in those at risk of stroke should not be prevented by elevated bleeding risk scores.